Synthesis of graft copolymers of cellulose with 4-acryloylmorpholine, 2-methacrylamidopyridine and N-phenylmethacrylamide, and determination of some sorption properties - Temuez, Mehmet Muersit; Coskun, Mehmet; Oelcuecue, Ali (Taylor & Francis Inc, 2007)
Some new cellulosic materials having water-and dye-uptake capacity and being suitable for the sorption of metal ions were synthesized by the grafting of cellulose with the amide monomers such as 4-acryloylmorpholine, 2-methacrylamidopyridine and N-phenylmethaerylamide. At first, cellulose methacrylate was prepared by esterification of primary -OH group with methacryloyl chloride with a 16.7% yield by mole. The amide monomers were grafted into cellulose methacrylate via free radical polymerization using alpha,alpha'-azobisisobutyronitrile (AIBN) as an initiator in acetonitrile. The graft copolymers were characterized by FT-IR spectra, elemental analyses and thermal analysis. Dye-uptake and dye-absorption properties of cellulose for alizarine yellow (basic dye) and bromocresol green (acidic dye), its moisture- and water-uptake capacities, and its metal ion sorption tendency (for Cu2+, Co2+ and Zn2+) improved with the grafting. A different behavior was observed for Ni2+ ion sorption.
Keywords: cellulose; graft copolymer; vinyl monomers; sorption properties